2016
DOI: 10.1002/cphc.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Blue‐Colored Solid‐State Dye‐Sensitized Solar Cells: Enhanced Charge Collection by Using an in Situ Photoelectrochemically Generated Conducting Polymer Hole Conductor

Abstract: A high power conversion efficiency (PCE) of 5.5 % was achieved by efficiently incorporating a diketopyrrolopyrrole-based dye with a conducting polymer poly(3,4-ethylenediothiophene) (PEDOT) hole-transporting material (HTM) that was formed in situ, compared with a PCE of 2.9 % for small molecular spiro-OMeTAD-based solid-state dye solar cells (sDSCs). The high PCE for PEDOT-based sDSCs is mainly attributed to the significantly enhanced charge-collection efficiency, as a result of the three-order-of-magnitude hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…However, Zhang et al demonstrated that the dye DPP07 is as efficient as LEG4 when combined with PEDOT, fabricating a device with a V OC of 770 mV, J SC of 11.13 mA cm À2 , FF of 65% and PCE of 5.54%. 475 Wang et al investigated the properties of a pre-polymerized block copolymer of poly(3-hexylthiophene) and poly(2,5-dihexyp-phenylene), and found that a PPP-b-P3HT-based solar cell achieved a V OC of 810 mV, J SC of 8.81 mA cm À2 , FF of 65% and PCE of 4.65%. 476 Liu et al investigated the performance of P3HT with two different dyes.…”
Section: Polymeric Hole Transporting Materialsmentioning
confidence: 99%
“…However, Zhang et al demonstrated that the dye DPP07 is as efficient as LEG4 when combined with PEDOT, fabricating a device with a V OC of 770 mV, J SC of 11.13 mA cm À2 , FF of 65% and PCE of 5.54%. 475 Wang et al investigated the properties of a pre-polymerized block copolymer of poly(3-hexylthiophene) and poly(2,5-dihexyp-phenylene), and found that a PPP-b-P3HT-based solar cell achieved a V OC of 810 mV, J SC of 8.81 mA cm À2 , FF of 65% and PCE of 4.65%. 476 Liu et al investigated the performance of P3HT with two different dyes.…”
Section: Polymeric Hole Transporting Materialsmentioning
confidence: 99%
“…Two years later Zhang et al also showed that the dye DPP07 is as efficient in combination with PEDOT as LEG4, when they fabricated a device with a V OC of 770 mV, J SC of 11.13 mA cm À2 , FF of 0.65 and PCE of 5.54%. 267 This device was much more efficient than a reference one based on spiro-OMeTAD (2.91%).…”
Section: Organic Hole Transporting Materialsmentioning
confidence: 89%
“…Such thin layers of noble metals such as Au/Ag not only collect charges from the HTM but reflect unabsorbed photons back into the active part of the cell. 267,303 Silver contacts generally exhibit stronger light reflection at a lower material cost. Gold contacts, however, excel with chemical stability and higher tolerance of minor defects in the HTM layer, while shunt resistances rapidly arise upon Ag penetration into the HTM layer.…”
Section: Counter Electrodementioning
confidence: 99%
“…The absorption band at 3415 cm -1 which was doled out to -OH group stretching vibration, moderately moved to 3375cm -1 with adding 1% wt of TiO2. This may be due to formation of hydrogen bonding between CMC and surface hydroxyl groups upon TiO2 [28]. Likewise, after the addition of TiO2, absorption bands at 692, 765 and 1062 cm -1 were shifted to 735, 796 and 1092 cm -1 , respectively.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 92%